2017
DOI: 10.1101/138263
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gravitational and dynamic components of muscle torque underlie tonic and phasic muscle activity during goal-directed reaching

Abstract: Human reaching movements require complex muscle activations to produce the forces necessary to move the limb in a controlled manner. How gravity and the complex kinetic properties of the limb contribute to the generation of the muscle activation pattern by the central nervous system (CNS) is a longstanding question in neuroscience. To address this question, muscle activity is often subdivided into static and phasic components. The former is thought to be related to posture maintenance and transitions between p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…We applied a simple and widely-used decomposition method to isolate the tonic (gravity-dependent force) and the phasic (inertial-dependent force) EMG components from the full EMG signal (Buneo et al, 1994; d’Avella et al, 2006, 2008; Flanders and Herrmann, 1992; Flanders et al, 1994, 1996; Olesh et al, 2017; Prange et al, 2009b, 2012; Russo et al, 2014). The tonic component emanates from the motionless rest-periods before and after the movement (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We applied a simple and widely-used decomposition method to isolate the tonic (gravity-dependent force) and the phasic (inertial-dependent force) EMG components from the full EMG signal (Buneo et al, 1994; d’Avella et al, 2006, 2008; Flanders and Herrmann, 1992; Flanders et al, 1994, 1996; Olesh et al, 2017; Prange et al, 2009b, 2012; Russo et al, 2014). The tonic component emanates from the motionless rest-periods before and after the movement (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We found that antigravity muscles exhibited periods of negativity precisely during the acceleration phase of a downward movement and the deceleration phase of an upward movement, when gravity can assist the movement (Figure 3 & 4). Notably, many studies already observed negativity of the phasic component of muscular activations and forces during vertical movements (Buneo et al, 1994; d’Avella et al, 2006, 2008; Flanders and Herrmann, 1992; Flanders et al, 1994, 1996; Olesh et al, 2017; Russo et al, 2014). However, this phenomenon was primarily ignored and attributed to erratic errors in the separation of noisy signals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic mechanical model of a human upper-limb (Olesh et al, 2017) was used to compute joint torques from joint motions. The model was constructed in Simulink (MathWorks, Inc.); it comprised three segments and five DOFs, including the shoulder (flexion/extension, abduction/adduction, internal/external rotation), elbow (flexion/extension), and wrist (flexion/extension).…”
Section: Task Dynamicsmentioning
confidence: 99%
“…The component of muscle torque that is responsible for intersegmental coordination can be extracted computationally. The inverse dynamic simulations used to estimate muscle torque can be ran without gravity, simulating the active torques necessary to produce the observed motion without gravity (Olesh et al 2017). This dynamic component of muscle torque also reflects the forces that are produced during planar reaches with gravitational support.…”
Section: Introductionmentioning
confidence: 99%